Degradation of The Mosque’s Roles in Maqashid Sharia Perspective - Nurul Jannah (Journal of Management and Business Innovations, 2021)
Looking at the maqashid sharia, the role of the mosque in the time of the Prophet was in the “tahsiniyah” position. However, in the modern era the role of the mosque was in the “dharuriyah” position, so the degradation of the mosques. This study aims to determine and understand the degradation of the mosque's role from the sharia maqashid's view and provide a renewal concept on the role of mosques in the modern era. This research is qualitative research using observation, questionnaires, and interviews. The analysis results show that the mosque building, and management still have not been felt by Muslims. By looking at the perspective of the sharia maqashid, Muslims still have not fulfilled their basic needs (dharuriyah needs), meaning that the welfare of worshipers is still low, which is a barrier to continuing the role of the mosque in the time of the Prophet. Then the findings of this study offer the concept of renewing the role of the perspective of the maqashid sharia mosque.Keywords: Degradation, maqashid syariah, mosque, role, welfare